A demonstration of appearance and union times of three shoulder ossification centers in adolescent and post-adolescent children. Issue 1 (March 2015) - Schaefer, Maureen; Aben, Gerald; Vogelsberg, Caitlin
Abstract It is well known that appearance and union times of epiphyseal/apophyseal elements can be used as a tool to estimate age in both living and deceased children. Radiographic documentation of ossification centers within the shoulder region however remains underexplored. This study fills that niche by recording the appearance and, or, union times of the proximal humerus, acromial process and coracoid angle/apex. Shoulder radiographs from 264 males and 189 females between the ages of 10 and 21 years were examined. These images were obtained via two sources including the Michigan State University׳s Clinical Center as well as Query Patricia, an online juvenile radiographic database. Developmental progress of each element was divided into a unique staging system based on the extent to which that center could be visualized. Observations were recorded for each of the three elements and their age/phase distributions are provided. A number of developmental milestones (phases) were observed to always occur before the age of 16 or 18 years. These results suggest that the shoulder region may be of particular value when evaluating the likely direction of an individual׳s age in relation to either of these two common threshold values.